KAJIAN SEMIOTIKA: MAKNA SIMBOLIK SULAPA’ EPPA DALAM MOTIF BALO LOBANG PADA LIPA’ SABBE BUGIS - Andi Fauziyah Hijrina Fatimah; Nurul Fadhillah; Andi Taslim Saputra (KAGANGA KOMUNIKA: Journal of Communication Science, 2026)
Lipa’ sabbe (Bugis silk sarong) is a textile that has been designated as an Intangible Cultural Heritage (ICH) of Indonesia since 2016. The balo lobang motif visually has a very close connection with the sulapa’ eppa (four sides) philosophy, which represents cosmological balance in the Bugis worldview. This research aims to uncover the symbolic meaning of sulapa’ eppa in the balo lobang motif on Bugis lipa’ sabbe. This type of research uses an interpretative qualitative research method, which seeks to find meaning in a phenomenon to investigate issues related to specific individuals, thereby gaining direct insight into their activities. The results of this study found interpretations related to the perspectives of representamen, object, and interpretation. This research outlines that the semiotic approach is crucial for understanding cultural artifacts as tools for generating meaning. According to the findings of this research, symbolic meanings must be revived in cultural practices. In this process, the symbolic values contained in the motifs tend to be simplified or even lose their relevance in social practice.   Keywords: Semiotics, Meaning, Lipa’ Sabbe, Balo Lobang, Sulapa’ Eppa